(untitled) (BIRDEM Medical Journal, 2023)
Background: Intrauterine fetal death (IUFD) is a cataclysmic event for the parents. It is an important indicator of maternal and perinatal health of a given population. This study was undertaken to study the maternal and fetal factors associated with IUFD. Methods: This was a retrospective study carried out in Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, from November 2019 to October 2020 . The details of history, examination findings, investigation reports , mode of delivery and fetal outcome were obtained from records. Results: A total number of 57 intrauterine fetal death were reported amongst 1534 deliveries conducted during the study period. The occurrence of intrauterine fetal death was 37.1/1,000 live births ; Among all these intrauterine fetal death cases, 87.7% deliveries were preterm and 89.4% deliveries were singleton delivery. The other associated maternal conditions were uncontrolled blood glucose in 64.9% cases, hypertensive disorders in 36.8% cases, other medical causes in 10.5% cases. Associated fetal conditions included intrauterine growth retardation of fetus in 28.0% cases, oligohydramnios in 21.0% cases, congenital malformation in 14.0 % cases. Placental condition included antepartum hemorrhage in 3.5% cases. Conclusions: In this study, the occurrence of intrauterine fetal death was associated with high incidence of uncontrolled blood glucose, oligohydramnios and congenital malformations . This emphases the importance of proper antenatal care and identification of risk factors and its proper treatment. BIRDEM Med J 2023; 13(2): 88-91